2010
DOI: 10.1111/j.1469-8137.2010.03422.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic acid mediates salt stress response by regulation of MPK6 in Arabidopsis thaliana

Abstract: • Phospholipase D (PLD) hydrolyzes phospholipids to produce phosphatidic acid (PA) and a head group, and is involved in the response to various environmental stresses, including salinity. Here, we determined the roles of PLDα and PA in the mediation of salt (NaCl)-stress signaling through the regulation of mitogen-activated protein kinase (MAPK or MPK) in Arabidopsis thaliana. • NaCl-induced changes in the content and composition of PA were quantitatively profiled by electrospray ionization-tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
321
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(332 citation statements)
references
References 58 publications
(155 reference statements)
10
321
0
1
Order By: Relevance
“…MAPK signaling triggers expression of a cascade of genes that are involved in cellular protection, desiccation tolerance, ROS scavenging enzymes and DNA damage repair by activating corresponding transcription factors (Neill et al 2002a, b;Hung et al 2005;Desikan et al 2000). Involvement of MAPKs in abiotic stress adaptation has been widely reported in many plant species (Yu et al 2010;Ning et al 2010 The transcript abundance of Nuclear Factor Y subunit A (NFYA) was found more in RRIM 600 and RRII 105 while it was moderate in RRII 208. But it got slightly down regulated in RRII 414.…”
Section: Resultsmentioning
confidence: 99%
“…MAPK signaling triggers expression of a cascade of genes that are involved in cellular protection, desiccation tolerance, ROS scavenging enzymes and DNA damage repair by activating corresponding transcription factors (Neill et al 2002a, b;Hung et al 2005;Desikan et al 2000). Involvement of MAPKs in abiotic stress adaptation has been widely reported in many plant species (Yu et al 2010;Ning et al 2010 The transcript abundance of Nuclear Factor Y subunit A (NFYA) was found more in RRIM 600 and RRII 105 while it was moderate in RRII 208. But it got slightly down regulated in RRII 414.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hoang et al (2012) have reported that the MAP kinase MPK6 activates, and interacts with, MYB41 and results in enhanced salt tolerance in Arabidopsis. In addition, the regulation of MPK6 by the phosphatidic acid (PA) under salt stress suggests that MPK6 and PA may function in the same signaling pathway in response to salt stress (Yu et al 2010).…”
Section: Mapks and Osmotic Stressmentioning
confidence: 99%
“…Moreover, the mkk2 mutant exhibits a salt-sensitive phenotype (Teige et al, 2004). A downstream target of MPK6 is the Na + /H + antiporter Salt Overly Sensitive1 (SOS1), a major regulator of ion homeostasis under salt stress (Shi et al, 1999;Yu et al, 2010). Furthermore, deregulated expression of MAPK genes alters the expression of salt stress-related TFs (KishiKaboshi et al, 2010;Kong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%